Composition and method for protective layer of metal electrode of secondary battery, and method

By coating the protective layer composed of organic binder and pyrolytic modified magnesium oxygen particles on the metal electrode of the lithium battery, the cycle stability and safety of the lithium battery are solved, and higher electrochemical performance and longer service life are achieved.

JP2025037820APending Publication Date: 2025-03-18EVONIK OPERATIONS GMBH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024141922
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-06
Filing Date
2024-08-23
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art has challenges in improving the cycle stability of lithium batteries, especially the problems of battery safety and stability caused by the high reactivity of lithium metal electrodes.

Method used

A protective layer consisting of an organic binder and modified magnesium oxygen particles by pyrolysis treatment is applied to the metal electrode of the lithium battery to improve the cycle stability of the battery.

Benefits of technology

Through the use of modified magnesium oxygen particles, the cycle stability and electrochemical performance of lithium batteries are significantly improved, the polarization voltage of the battery is reduced, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037820000001_ABST
    Figure 2025037820000001_ABST
Patent Text Reader

Abstract

To provide a composition for an electrode coating layer that improves cycle stability of a secondary battery such as a lithium metal battery, an electrode, and a method of manufacturing the electrode.SOLUTION: A composition for an electrode coating layer of a secondary battery, particularly, a lithium battery includes: an organic binder; and a metallic compound that is selected from the group consisting of surface-modified magnesium oxide, surface-modified lithium dope magnesium oxide, surface-modified magnesium phosphate, or a mixture of them.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates generally to compositions and methods for protective layers for electrodes of secondary batteries, particularly lithium batteries. The present invention further relates to such electrodes and secondary batteries, particularly lithium batteries, using such electrodes with protective layers. The method further relates to electronic or electrical devices using such secondary batteries, particularly lithium batteries. [Background technology]

[0002] Lithium metal batteries (LMBs), such as lithium-sulfur (Li-S) batteries, lithium-air (Li-air) batteries, and solid-state lithium batteries, have been reported to overcome at least some of the drawbacks of lithium-ion batteries, such as the lack of high energy storage capacity. However, the inherent properties of metallic lithium can lead to issues regarding battery safety and instability, limiting the cycle life. The highly reactive nature of lithium induces various processes that generally negatively affect the cycle life of batteries, such as degradation of liquid electrolytes, formation of solid electrolyte interface (SEI), corrosion of lithium cathodes due to the presence of traces of water in the electrolyte, formation of lithium dendrites, and lithium deactivation due to the polysulfide shuttle effect in Li-S batteries. Therefore, successful stabilization / protection of lithium cathodes is highly desirable for the further development of LMB technology.

[0003] A recent approach to stabilizing the lithium metal-electrolyte interface with soft polymer coatings has shown the potential to improve the rate and capacity of lithium metal cycling. Thus, it has been disclosed that the controlled protection of the lithium cathode with organic and / or inorganic materials has a beneficial effect on the battery performance.

[0004] CN109473627 describes the preparation of a composite electrode containing lithium metal, inorganic nano-materials such as titanium oxide, alumina, silica, boehmite, zirconia, etc., with particle sizes of 50-500 nm, organic polymer, and membrane material, by the following steps: (1) preparing a solution of polymer and inorganic particles, (2) coating the solution on the membrane surface and then drying, (3) grinding the dried composite material prepared in step (2) with metallic lithium to form composite electrode particles covered with a composite layer, and (4) molding the composite electrode material to form a metallic lithium electrode sheet containing lithium particles covered with a protective layer.

[0005] US Patent Publication No. 20170062829 describes a lithium metal battery including a lithium metal anode with a protective layer including a polymer (e.g., a styrene-isoprene copolymer), at least one metal salt, and a nitrogen-containing additive such as Li3N. The protective layer may also include inorganic particles such as TiO2, ZnO, Al2O3, SiO2, etc., with unspecified particle sizes of about 1-500 nm.

[0006] US Patent Publication No. 20140220439 describes an alkali metal cathode coated with a protective coating comprising inorganic particles containing the elements Al, Mg, Fe, Sn, Si, B, Cd, Sb dispersed throughout a matrix of an organic compound, such as a pyrrolidine derivative.

[0007] US Patent Publication No. 20170301920 describes lithium metal electrodes coated with a protective layer comprising a polymeric ionic liquid and, optionally, inorganic nanoparticles such as SiO2, Al2O3, TiO2, MgO, ZrO2, ZnO, Fe3O4, barium titanate, lead titanate, lithium nitride, lithium aluminate, and the like.

[0008] Jang et al. reported in Adv. Funct. Mater. 2019, Vol. 29(48), No. 1905078 that the Zr Odescribes the preparation of a coated lithium metal cathode, which involves mixing Al2O3 powder or Al2O3 powder with an average particle size of 500 nm with polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) polymer, DMF, and electrolyte, and applying the slurry to a lithium metal foil with a thickness of 450 μm and drying to form a coating layer with a thickness of 21.7 μm.

[0009] US Patent Publication No. 20180316051 describes a negative electrode for a lithium metal battery that includes a lithium metal layer, a lithium metal alloy, and a protective layer having inorganic particles with a particle size greater than about 1 μm and less than or equal to about 100 μm.

[0010] WO2019149939 describes a lithium metal cathode coated with a protective layer having a thickness of 0.01-10 μm, which comprises a polymer and up to 30% by weight of inorganic particles (Al2O3, MnO, MnO2, SiO2, TiO2, ZnO, ZrO2, Fe2O3, CuO, silicates, aluminosilicates, borosilicates, etc.) with an average particle size of 1-500 nm.

[0011] Lee, Y., Fujiki, S., Jung, C. et al., Nature Energy, vol. 5, pp. 299-308 (2020), describe a high-performance all-solid-state lithium metal battery with a sulfide electrolyte and a composite Ag-C cathode without excess lithium. The metal layer of the composite Ag-C cathode in this system allows for effective control of Li deposition, resulting in long electrochemical cyclability. Thus, in this case, instead of a conventional lithium cathode, a silver-based cathode is used, on which a lithium layer is reversibly deposited during the operation of the lithium battery.

[0012] US20200106103 describes a protective layer material that includes a polymer or a mixture of a polymer and an inorganic material selected from the group consisting of HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, BaO, ZnO, ZrO2, Al2O3, TiO2, SiO2, Li3PO4, Li2O, LiF, LiOH, Li2CO3, Li-containing metal oxides, Li-containing phosphates, and any combination thereof.

[0013] WO2021144299 describes a lithium metal cathode coated with a protective layer having a thickness of 0.5 to 500 μm. The protective layer comprises a polymer and a metal compound selected from the group consisting of aluminum oxide, silicon dioxide, zirconium oxide, mixed oxides containing zirconium, mixed oxides containing aluminum, lithium zirconium phosphate, and mixtures thereof. The metal compound consists of strong agglomerates of primary particles obtained by pyrolysis and having an average primary particle size d50 of 5 nm to 100 nm.

[0014] Challenges and Solutions WO2021144299 teaches that the larger the BET surface area of ​​nano-sized metal oxide particles, the better the electrochemical performance of lithium metal batteries. However, the larger the BET surface area of ​​the metal oxide particles in the protective layer, the more difficult it is to obtain a stable coating dispersion and coating slurry on the metal cathode.

[0015] Importantly, the physicochemical properties of the inorganic particles used in protective coatings or layers on metallic lithium electrodes, such as particle type, particle size, particle size distribution, strong and weak agglomerations, particle surface, and the content of such particles, affect the chemical stability of the metallic lithium electrode during cycling of a lithium metal battery. [Prior art documents] [Patent documents]

[0016] [Patent Document 1] China Patent Application Publication No. 109473627 [Patent Document 2] US Patent Publication No. 20170062829 [Patent Document 3] US Patent Application Publication No. 20170301920 [Patent Document 4] US Patent Publication No. 20180316051 [Patent Document 5] International Publication No. 2019149939 Brochure [Patent Document 6] US Patent Publication No. 20200106103 [Patent Document 7] International Publication No. 2021144299 Brochure Summary of the Invention [Problem to be solved by the invention]

[0017] The problem addressed by the present invention is a method for increasing the cycling stability of secondary batteries such as lithium batteries, in particular lithium metal batteries. [Means for solving the problem]

[0018] The present invention provides an improved composition for the protective layer of the metal electrode of a secondary battery that improves the cycling stability of secondary batteries, particularly lithium batteries, and more particularly lithium metal batteries.

[0019] Summary of the Invention The present invention generally relates to a composition and method for a protective layer of a metal electrode of a secondary battery, a metal electrode, a secondary battery using said electrode, and an electronic or electric device using said secondary battery as defined in the independent claims. Embodiments of the invention are defined in the dependent claims. Features of one embodiment can be combined with one or more features of the other embodiments, unless they are mutually inconsistent.

[0020] In the course of extensive experimentation, it was surprisingly found that the combination of an organic binder with pyrogenically produced surface-modified magnesium oxide particles is particularly suitable for coating metal electrodes, for example lithium electrodes in lithium-ion batteries.

[0021] These and other features and advantages of the present invention will become apparent from the following description and drawings. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a simplified diagram of an electrode according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a flow chart of a method for manufacturing an electrode according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a simplified diagram of a secondary battery according to one embodiment of the present invention. [Figure 4] FIG. 4 is a simplified diagram of an electronic or electrical device according to one embodiment of the present invention. [Diagram 5] FIG. 5 shows the cycle of polarization voltage at a current density of 1 mA / cm 2 when AEROXIDE® Alu 130 was used as a filler in the protective layer on the Li layer (Comparative Example 1). [Figure 6] FIG. 6 shows the polarization voltage cycles at a current density of 1 mA / cm2 when Alu 130 805 was used as the filler in the protective layer on the Li layer (Example 6). [Figure 7] FIG. 7 shows the cycle of polarization voltage at a current density of 1 mA / cm 2 when Alu 200 was used as the filler in the protective layer on the Li layer (Example 7). [Figure 8] FIG. 8 shows the cycle of polarization voltage at a current density of 1 mA / cm 2 when MgO-01 was used as a filler in the protective layer on the Li layer (Example 8). [Figure 9] FIG. 9 shows the cycle of polarization voltage at a current density of 1 mA / cm 2 when MgO 805 was used as the filler in the protective layer on the Li layer (Example 10). [Figure 10]FIG. 10 shows the polarization voltage cycle at a current density of 1 mA / cm 2 in the absence of a protective layer (Comparative Example 2). [Figure 11] FIG. 11 shows the polarization voltage at the 200th cycle at a current density of 1 mA / cm2 for various experimental examples.

[0023] Detailed Description of the Invention 1, an electrode 11 for a secondary battery according to one embodiment of the present invention is provided. The electrode 11 comprises a metal layer 10 coated with a coating layer 14. The coating layer 14 includes an organic binder "OB" and a metal compound "MC".

[0024] The metal compound MC is selected from the group consisting of hydrophobic surface-modified fumed magnesium oxide, hydrophobic surface-modified lithium-doped fumed magnesium oxide, hydrophobic surface-modified fumed magnesium phosphate, and mixtures thereof.

[0025] The metal compounds MC are obtained by pyrolysis (also called "fume" or "fumed") methods. Pyrolysis methods in the context of this specification may include flame oxidation, flame hydrolysis, or flame pyrolysis. Such methods generally involve the oxidation or hydrolysis of hydrolyzable or oxidizable starting materials in a hydrogen and / or oxygen flame. Preferably, the pyrolysis can be flame spray pyrolysis. An example of the flame spray pyrolysis method is described in WO 2015173114 by Katusic et al., entitled "Method for Producing Mixed Oxide Powders Containing Lithium, Lanthanum, and Zirconium" and U.S. Patent Application Publication No. 2022 / 0306485 by Shafer et al., entitled "Preparation of Nanostructured Mixed Lithium Zirconium Oxides by Spray Pyrolysis." The flame spray pyrolysis process preferably comprises the following steps: atomizing at least one metal precursor solution with an atomizing gas to generate an aerosol; reacting the aerosol with a flame obtained by ignition of a mixture of a fuel gas and an oxygen-containing gas in a reaction space of a reactor to obtain a reaction stream; cooling the reaction stream; and Thereafter, removing solid metal oxide from the reaction stream.

[0026] Thus, flame spray pyrolysis (FSP) may include atomizing a solution of metal precursors, such as magnesium chloride, magnesium sulfate, magnesium carbonate, magnesium hydroxide, magnesium lactate, magnesium citrate, magnesium glutamate, and magnesium aspartate, in an atomizer (also called vaporizer) and supplying the vapor to a mixing chamber. The vapor may be transported to the mixing chamber via an inert carrier gas. Separately, a fuel gas including hydrogen and primary air may be introduced into the mixing chamber. The air may be enriched with oxygen, if necessary. The air may be preheated, if necessary, before being supplied to the mixing chamber. Hydrogen may be preferably used in slight excess to the stoichiometric amount required for the production reaction.

[0027] The magnesium oxide powder produced from the FSP can then be separated from the gas in a downstream gas-solid separation unit and deposited at the bottom of the gas-solid separation unit (e.g., a cyclone) and collected via the bottom outlet. The resulting powder is transferred to a deacidification device for removing acids from the powder, in which the magnesium oxide powder is treated with air and steam supplied in a countercurrent direction at high temperatures of 100°C to 700°C, more preferably 150°C to 650°C, even more preferably 200°C to 600°C, even more preferably 250°C to 550°C. The powder is collected in a silo and can be further processed as required, for example, compacted.

[0028] Suitable starting materials for pyrolysis may include organic and / or inorganic magnesium compounds, such as magnesium chloride, magnesium nitrate, magnesium acetate, and magnesium carboxylate. For example, in flame hydrolysis, a metal precursor, such as magnesium chloride, is typically vaporized and reacted in a flame generated by the reaction of hydrogen and oxygen to produce magnesium oxide particles. The resulting powder is referred to as a "pyrolyzed" or "fumed" magnesium oxide metal compound.

[0029] The reaction initially produces highly dispersed primary particles which, during the further course of the reaction, aggregate to form agglomerates, i.e. strongly bonded primary particles, and weak agglomerates, which are relatively weakly bonded aggregates. The agglomerate sizes of these powders are generally in the range of 0.05 μm to 50 μm.

[0030] These powders can be converted into particles in the nanometer (nm) range suitable for the purposes of the present invention by suitable grinding, which breaks down the weak agglomerates but does not substantially alter the strong agglomerates of the primary particles.

[0031] The metal compound (e.g., magnesium oxide) used in the present invention preferably has a specific surface area (BET) of 1 m 2 / g~500m 2 / g, more preferably 20m 2 / g~400m 2 / g, more preferably 40m 2 / g~350m 2 / g, most preferably 50m 2 / g~300m 2 / g.

[0032] The specific surface area, also known simply as the BET surface area, can be determined by nitrogen adsorption according to the Brunauer-Emmett-Teller method in accordance with DIN 9277:2014.

[0033] In some embodiments, the product of the pyrolysis process is further heat treated at a temperature between 100 and 350°C.

[0034] In some embodiments, mixed metal oxides including magnesium oxide may be used. For example, the mixed oxides may include magnesium oxide, lithium-doped magnesium oxide, magnesium phosphate, or mixed oxides or phosphates including lithium, magnesium, phosphorus, and oxygen. These compounds are simply referred to as metal compounds MC.

[0035] The particles of the metal compound used in the present invention are obtained by a pyrolysis method, and usually, most of the particles are in the form of strong aggregates, but some particles may be in the form of non-strongly aggregated primary particles. The metal compound MC preferably has a number average strongly aggregated particle diameter d50 of less than 2 μm, preferably 20 nm to 1 μm, more preferably 30 nm to 800 nm, even more preferably 40 nm to 600 nm, and most preferably 50 nm to 500 nm. The number average particle diameter d50 can be measured by a static light scattering (SLS) method in a suitable dispersion, for example, an aqueous dispersion.

[0036] In some embodiments, the weak aggregates and some of the strong aggregates can be broken, for example, by grinding or ultrasonicating the powder obtained by the pyrolysis method, resulting in particles with smaller particle size and narrower particle size distribution. In such an embodiment, a mixture of 5% by weight of the ground metal compound particles and 95% by weight of 0.5 g / L aqueous sodium pyrophosphate solution is ultrasonicated at 25°C for 300 seconds, and then the strong aggregate particle size d50 measured by dynamic light scattering (DLS) or static light scattering (SLS) is 50 nm to 1000 nm, more preferably 100 nm to 700 nm, and even more preferably 150 nm to 500 nm.

[0037] Furthermore, the powder obtained by pulverizing or ultrasonicating the powder obtained by the pyrolysis method is a mixture consisting of 5 wt. % of the particles and 95 wt. % of a 0.5 g / L aqueous solution of sodium pyrophosphate, and then ultrasonicated at 25°C for 300 seconds. The span, defined as (d90-d10) / d50, measured by static light scattering (SLS) is preferably 0.4 to 1.2, more preferably 0.5 to 1.1, and even more preferably 0.6 to 1.0.

[0038] Thus, the metal compounds MC present in the coating layer 14 of the electrode 11 of the invention are preferably characterized by a relatively small average strongly agglomerated particle size d50 and a narrow particle size distribution (d90-d10) / d50, which helps to achieve a high quality metal compound coating of the lithium electrode.

[0039] The d-values ​​d10, d50, and d90 are commonly used to characterize the cumulative particle size distribution of a particular sample. For example, the d10 diameter is the diameter where 10% of the sample's volume is made up of particles smaller than d10, and the d50 is the diameter where 50% of the sample's volume is made up of particles smaller than d50. The d50 is also called the "volume median diameter" because it divides the sample evenly by volume. The d90 is the diameter where 90% of the sample's volume is made up of particles smaller than d90.

[0040] The tamp density of the metal compound present in the electrode of the present invention may be 20 g / L to 1000 g / L. The tamp density of the non-heat-treated metal compound is preferably 20 g / L to 200 g / L, more preferably 25 g / L to 150 g / L, even more preferably 28 g / L to 130 g / L, and even more preferably 30 g / L to 120 g / L.

[0041] The tamp density of fine or coarse granulates can be measured according to DIN ISO 787-11:1995 "General methods for testing pigments and extenders - Part 11: Determination of tamp volume and apparent density after tamping", which includes the measurement of the apparent density of the bed after stirring and tamping.

[0042] Surface-treated metal compounds The metal compound MC present in the coating layer 14 of the electrode 11 according to the present invention is subjected to a surface treatment, in particular a hydrophobic surface treatment, in order to improve the compatibility of the metal compound particles with the organic binder OB and the solvent used in the coating process.

[0043] Therefore, the metal compound MC present in the coating layer 14 of the electrode 11 may be hydrophobic and have a methanol wettability in which the methanol content in the methanol / water mixture is greater than 5%, preferably 10% to 80%, more preferably 15% to 70%, even more preferably 20% to 65%, and most preferably 25% to 60%.

[0044] The term "hydrophobic" or "hydrophobized" in the present context relates to particles that have a low affinity for polar media such as water. In contrast, hydrophilic particles have a high affinity for polar media such as water.

[0045] The hydrophobicity of hydrophobic materials can be achieved by applying suitable non-polar groups to the surface of the particles. The degree of hydrophobicity of metal compounds can be measured by parameters including methanol wettability, as described in detail, for example, on pages 5-6 of WO 2011 / 076518. In pure water, the hydrophobic particles of the metal compound completely separate from the water and float on the water surface without being wetted by the solvent. In contrast, in pure methanol, the hydrophobic particles are dispersed throughout the entire volume of the solvent and are completely wetted. In the measurement of methanol wettability, the maximum methanol content at which the metal compound is not yet wetted is measured in the methanol / water test mixture. This means that 100% of the metal compound used remains separated from the test mixture in an unwetted state after contact with the test mixture. This methanol content in the methanol / water mixture (in vol. %) is called the methanol wettability. The higher the level of methanol wettability, the more hydrophobic the metal compound is. The lower the methanol wettability, the less hydrophobic and more hydrophilic the metal compound is.

[0046] Specifically, to measure the methanol wettability, 0.2 g (±0.005 g) of each surface-treated particle is weighed into a clear centrifuge tube. Methanol / water mixtures (8.0 mL) containing 10%, 20%, 30%, 40%, 50%, 60%, 70% or 80% methanol by volume are added to each sample. The tubes are shaken for 30 seconds and then centrifuged at 2500 rpm for 5 minutes. Methanol wettability is defined as the volume fraction of methanol that results in 100% of the precipitate volume. The higher the number, the more hydrophobic the precipitate is.

[0047] The metal compounds of the present invention are preferably surface-treated with a surface treatment agent selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes, and mixtures thereof, and are thus hydrophobized.

[0048] The hydrophobic metal compound preferably has a carbon content of 0.1% to 15.0% by weight, more preferably 0.5% to 12.0% by weight, even more preferably 1.0% to 10.0% by weight, most preferably 1.5% to 8.0% by weight. The carbon content can be determined by elemental analysis according to EN ISO3262-20:2000-Chapter 8. The analyzed sample is weighed into a ceramic crucible supplied with a combustion additive and heated in an induction furnace under a flow of oxygen. The carbon present is oxidized to CO2. The amount of CO2 gas is quantified by an infrared detector.

[0049] metal layer The term "layer" in the context of this specification means a continuous deposition of the corresponding substance or component on the surface of another substance or component.

[0050] The metal layer 10, e.g., lithium layer, of the electrode 11 of the present invention may be further supported on a metal foil 8, which functions as a current collector. This metal foil 8 may include lithium, sodium, potassium, magnesium, calcium, zinc, aluminum, copper, silver, gold, nickel, iron, indium, gallium, steel, stainless steel, titanium, or metal alloys thereof. Such metal alloys may also include non-metallic components, e.g., silicon, germanium, etc. Most preferably, the metal foil 8 may include copper or aluminum, especially when the electrode of the present invention is used in combination with a liquid electrolyte. Stainless steel foils may preferably be used for electrodes used in combination with solid electrolytes, e.g., sulfide electrolytes. The thickness of the metal foil 8 may be 0.5 μm to 500 μm, more preferably 1 μm to 100 μm, even more preferably 2 μm to 50 μm, and most preferably 5 μm to 30 μm. In some embodiments, the metal foil 8 may be further supported on a polymer substrate (not shown).

[0051] According to one embodiment of the present invention, the thickness of the metal layer 10 of the electrode 11 may be preferably 2 μm to 500 μm, more preferably 3 μm to 300 μm, even more preferably 5 μm to 200 μm, and most preferably 7 μm to 180 μm.

[0052] Metal layer 10 may be disposed on metal foil 8 by any suitable method, such as vacuum deposition, rolling, electrochemical deposition, or lamination, which are well known in the industry and will not be described in detail.

[0053] Coating Layer Coating layer 14 of electrode 11 comprises an organic binder OB and a metal compound MC selected from the group consisting of hydrophobic surface-modified fumed magnesium oxide, hydrophobic surface-modified lithium-doped fumed magnesium oxide, hydrophobic surface-modified fumed magnesium phosphate, or mixtures thereof.

[0054] In the coating layer 14, the weight ratio of the metal compound MC to the organic binder OB is 0.1 to 10, preferably 0.2 to 9.5, more preferably 0.3 to 9.0, even more preferably 0.4 to 8.5, even more preferably 0.5 to 8.0, even more preferably 0.8 to 7.0, and most preferably 1.0 to 6.0.

[0055] electrode Electrode 11 according to embodiments of the present invention may include a lithium salt that may be optionally added to coating layer 14. For example, in some embodiments, the lithium salt may be mixed together with organic binder OB and metal compound MC, and then the mixture may be applied to metal layer 10 of electrode 11.

[0056] The lithium salt may be selected from the group consisting of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium triflate, lithium bis(perfluoroethylsulfonyl)imide (LiN(SO2CF2CF3)2), lithium nitrate, lithium bis(oxalo)borate, cyclo-difluoromethane-1,1-bis(sulfonyl)imide lithium, cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide lithium, and mixtures thereof.

[0057] Lithium bis(fluorosulfonyl)imide (LiFSI) or lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) may preferably be used as the lithium salt of the coating layer 14 in batteries using solid electrolytes.

[0058] According to an embodiment, the thickness of the coating layer may be from 0.1 μm to 300 μm, more preferably from 0.5 μm to 100 μm, even more preferably from 1 μm to 50 μm, and most preferably from 2 μm to 20 μm.

[0059] Organic Binder The organic binder OB for the electrolyte coating layer 14 provides effective adhesion between the particles of the metal compound MC in the coating layer 14 and the surface of the metal layer 10 (eg, lithium layer 10).

[0060] The organic binder is selected from the group consisting of poly(vinylidene fluoride), copolymers of vinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), poly(ethylene oxide), poly(methyl methacrylate), poly(ethyl acrylate), poly(vinyl chloride), poly(urethane), poly(acrylonitrile), poly(ethylene glycol), polypropylene glycol, poly(ethylene glycol-co-propylene glycol-co-ethylene glycol), poly(propylene glycol-co-ethylene glycol-co-propylene glycol), polysiloxanes, poly(oxyethylene)methacrylate, poly(ethylene glycol)diacrylate, poly(propylene glycol)diacrylate, poly(ethylene glycol)dimethacrylate, poly(propylene glycol)dimethacrylate, poly(ethylene glycol)-dimethyl ether, poly(ether amines), copolymers of ethylene and vinyl acetate, carboxymethyl cellulose, poly(imides), and mixtures thereof.

[0061] More preferably, the organic binder can be either PVDF or PVDF-HFP. In particular, PVDF-HFP is suitable for coating on lithium (Li) metal layers, and PVDF is suitable for other metal layers, such as copper (Cu) layers / foils.

[0062] Electrode manufacturing method Referring to FIG. 2, according to one embodiment of the present invention, there is provided a method for manufacturing an electrode 11 of the present invention, the method comprising: In step 102, a mixture is prepared containing the above-mentioned organic binder OB and the above-mentioned metal compound MC obtained by a pyrolysis method, in step 104, the mixture prepared in step 102 is applied to the surface of the metal layer 10 to form a pre-coating layer, and in step 106, the pre-coating prepared in step 104 is dried and / or cured to form the coating layer 14. In one embodiment, a lithium salt may be added and then mixed with the organic binder OB and metal compound MC in step 102 of preparing a mixture of the organic binder OB and metal compound MC. In embodiments where a semi-solid or solid electrolyte is used, the addition of a lithium salt along with the organic binder and metal compound MC can improve Li-ion conductivity in the protective layer since no liquid is present in the protective layer.

[0063] The metal compound MC is selected from the group consisting of hydrophobically surface-modified fumed magnesium oxide, hydrophobically surface-modified fumed lithium-doped magnesium oxide, hydrophobically surface-modified fumed magnesium phosphate, and mixtures thereof. The lithium salt is selected from the group consisting of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium triflate, lithium bis(perfluoroethylsulfonyl)imide (LiN(SO2CF2CF3)2), lithium nitrate, lithium bis(oxalo)borate, cyclo-difluoromethane-1,1-bis(sulfonyl)imide, cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide, and mixtures thereof.

[0064] The metal compound includes the powder obtained by pyrolysis as described above. Preferably, the powder obtained by pyrolysis can be subjected to grinding or ultrasonic treatment and surface modification treatment to further reduce the particle size of the powder and make them hydrophobic. The weight ratio of the metal compound to the organic binder is 0.1 to 10, preferably 0.2 to 9.5, more preferably 0.3 to 9.0, more preferably 0.4 to 8.5, more preferably 0.5 to 8.0, more preferably 0.8 to 7.5, more preferably 1.0 to 6.0.

[0065] In step 102 of the method of the present invention, a solvent can be used as needed, and is not particularly limited, as long as it dissolves the organic binder OB during the coating process and does not react with the metal compound (e.g., lithium metal). A non-exhaustive list of suitable solvents may include 1,2-dimethoxyethane, diethyl ether, tetrahydrofuran, dioxane, bis(2-methoxyethyl)ether, pentane, hexane, heptane, octane, decane, toluene, ethanol, isopropanol, N-methyl-2-pyrrolidone, triethyl phosphate, dimethyl sulfoxide, methyl ethyl ketone, methyl isobutyl ketone, benzaldehyde, N,N-dimethylformamide, dimethylacetamide, acetonitrile, cyclohexanone, ethyl acetate, propylene carbonate, ethylene carbonate, diethylene glycol monomethyl ether, triethylene glycol methyl ether, acetylacetone, acetone, and mixtures thereof.

[0066] The mixture prepared in step 102 of the method according to the invention may be obtained from two or more mixtures. For example, a first mixture may comprise metal compound particles and a first solvent, and a second mixture may comprise an organic binder, a second solvent, and optionally a lithium salt. The first and second solvents may be the same or different. The first and second solvents may preferably be the same.

[0067] Preferably, the first mixture may contain 1 wt% to 70 wt%, more preferably 3 wt% to 60 wt%, even more preferably 5 wt% to 50 wt%, and most preferably 7 wt% to 45 wt% of the metal compound, and 30 wt% to 99 wt%, more preferably 40 wt% to 97 wt%, even more preferably 50 wt% to 95 wt%, and most preferably 55 wt% to 93 wt% of the solvent. The second mixture may contain 0.1 wt% to 90 wt%, preferably 0.5 wt% to 50 wt%, more preferably 1 wt% to 20 wt%, and more preferably 2 wt% to 10 wt% of the organic binder, and 10 wt% to 99.9 wt%, preferably 50 wt% to 99.5 wt%, more preferably 80 wt% to 99 wt%, and more preferably 90 wt% to 98 wt% of the solvent.

[0068] In step 104 of the method of the present invention, the metal layer 14 is coated with the mixture prepared in step 102 to form a pre-coating layer on the surface of the metal layer 14, the pre-coating layer including a metal compound and an organic binder.

[0069] Any suitable coating method capable of applying a relatively thin coating layer may be used. An example of a suitable device for the coating process is the doctor blade device SA-202 available from the manufacturer Tester Sangyo.

[0070] The precoat layer on the metal layer 14 in step 104 is further dried and / or cured on the surface of the metal layer 14 in step 106 of the method of the present invention, thereby forming a coated metal layer 14 on the metal layer 10 of the electrode 11.

[0071] Hardening of the mixture of the precoat layer can occur, for example, by polymerization, crosslinking reaction, or other type of chemical reaction, or by physical hardening, for example, evaporation of the solvent or other volatile components of the binder. Chemical hardening can occur, for example, by heat or under the action of ultraviolet or other radiation.

[0072] Depending on the system used, step 106 may be carried out at a temperature preferably between 0° C. and 500° C., more preferably between 5° C. and 400° C., more preferably between 10° C. and 300° C., more preferably between 20° C. and 150° C. Drying / curing step 106 may be carried out in the presence of air or, preferably to the exclusion of oxygen, under a protective gas atmosphere, for example nitrogen or argon. Drying / curing step 106 may be carried out under standard pressure. Drying / curing step 106 may be carried out under reduced pressure, for example under vacuum.

[0073] Use of electrodes The present invention further relates to the use of the electrode 11 of the present invention as a component of a lithium metal battery, a lithium ion battery, or other secondary battery, preferably a lithium metal battery or a lithium ion battery, more preferably a lithium metal battery.

[0074] FIG. 3 shows a lithium metal battery generally designated by the numeral 40, including separators 16, 18, a first electrode 11, and a second electrode 20, 22. The first electrode 11 corresponds to the electrode 11 of the present invention of FIG. 1, with a coating layer 14, a metal layer 10, and a foil 8. The coating layer 14 includes an organic binder OB and a metal compound MC as described above, and may include a lithium salt in some embodiments. The coating layer 14 may preferably be in the form of a nanoparticle powder. The coating layer 14 may be formed on the metal layer 10 of the electrode 1 of FIG. 1. The thickness of the coating layer 14 may be 0.1 μm to 300 μm, more preferably 0.5 μm to 100 μm, even more preferably 1 μm to 50 μm, and most preferably 2 μm to 20 μm. An electrolyte 24 is disposed around the separators 16, 18 and between the first and second electrodes. The separators 16, 18 may include, for example, a polymer membrane 16 covered on both sides with a ceramic coating 18. As shown generally in Figure 4, the lithium metal battery 40 may be used in electronic and electrical devices 400 such as cell phones, computers (laptop computers, desktop computers, computer pads), electronic watches, key fabs, appliances, power tools, vacuum cleaners, electric lawnmowers, electric vehicles, to name just a few of the many applications of lithium batteries. The second electrode 20, 22 may comprise an active material 20 on an electrode plate 20.

[0075] In some embodiments, the method may include operatively connecting a first electrode 11 in a secondary battery 40 as a positive electrode of the secondary battery 40. The secondary battery 40 may be provided in an electronic or electrical device 400 to provide power to the device 400. EXAMPLES

[0076] Metal Compound Samples: AEROXIDE® Alu130 is a commercial product from Evonik Operations GmbH. Alu130 805 is a fumed alumina particle surface modified with Dynasylan® OCTMO (octyltrimethoxysilane) and has a BET surface area of ​​130 m 2 / g. Alu200 is a zeolite with a BET surface area of ​​200 m, produced by gas phase synthesis. 2 / g of fumed aluminum oxide particles. MgO-1 is a 70m BET alloy produced by flame spray pyrolysis. 2 / g of fumed magnesium oxide particles. MgO-8 is produced by flame spray pyrolysis and has a BET of 246m. 2 / g of fumed magnesium oxide particles. MgO805 is surface modified with Dynasylan® OCTMO (octyltrimethoxysilane) and has a BET of 234m 2 / g of magnesium oxide particles.

[0077] Preparation of metal oxide particles: Comparative Example 1: Preparation of surface-modified aluminum oxide Alu 130 805 300 g of pyrogenically produced aluminum oxide particles, designated AEROXIDE® Alu 130, were placed in a mixer and 48 g of octyltrimethoxysilane (C 11 H 26 After the powder was sprayed with the silane, mixing was continued for an additional 5 minutes. The wet powder was then conditioned in an oven at 130°C for 3 hours. The particle characteristic data of the hydrophilic surface modified aluminum oxide are shown in Table 1.

[0078] Comparative example 2: Alu 200 Aluminum trichloride (AlCl3) was first vaporized as a raw material precursor, and the vapor phase AlCl3 (0.8 kg / h) was transferred to the mixing chamber. 3 / hour combustion gas H2, 6.6m 3 / hr primary air was introduced into the mixing chamber. The reaction mixture was fed to a burner through a central tube and ignited. The flame was burned in a water-cooled reaction chamber. A 4.5 m 3 / hr secondary air was also introduced into the reaction chamber. The resulting powder was deposited on a downstream filter and then treated in counter-flow air and steam at about 660° C. The particle characteristics of the resulting powder are shown in Table 1.

[0079] Comparative Example 3: Production of Magnesium Oxide (MgO-01) by Pyrolysis 8.0 kg of an aqueous solution (Mg(NO3)2·6H2O) containing 480 g of magnesium nitrate was prepared. 2.5 kg / h of this dispersion and 15 Nm 3 Aerosols of air and 10000g / hr were generated using a two-component nozzle and sprayed into a tubular reactor with a combustion flame. The combustion gases of the flame were 16 Nm 3 / hour hydrogen and 30Nm 3 / hour air and 25Nm 3 / hr secondary air was used. After the reactor the reaction gas was cooled and filtered. The particle characteristics of the resulting powder are shown in Table 1.

[0080] Comparative Example 4: Preparation of pyrogenically produced magnesium oxide (MgO-08) with high BET surface area 1.89 kg of an aqueous solution containing 1000 g of magnesium acetate hydrate (Mg(CH3COO)2*4H2O) was prepared. 2.5 kg / h of this dispersion and 15 Nm 3 Aerosols with air / hour were generated using a two-component nozzle and sprayed into a tubular reactor with a combustion flame. The combustion gases of the flame were 8 Nm 3 / hour hydrogen and 30Nm 3 / hour air and 25Nm 3 / hr secondary air was used. After the reactor, the reaction gas was cooled and filtered. The resulting high surface area pyrogenically produced hydrophilic magnesium oxide has the physical property data shown in Table 1.

[0081] Example 1: Preparation of surface-modified magnesium oxide (MgO-805) 300 g of pyrogenically produced magnesium oxide (Example 4) was placed in a mixer and 72 g of octyltrimethoxysilane (C 11 H 26After the powder was sprayed with the silane, mixing was continued for an additional 5 minutes. The wet powder was then conditioned in an oven at 130°C for 3 hours. The hydrophilic surface modified magnesium oxide has the physical and chemical property data shown in Table 1. Table 1: Physical properties of the metal compound particles tested

[0082] [Table 1]

[0083] Preparation of coated electrode plates Comparative Example 5 A 12 μm thick copper foil was prepared, covered with a 100 μm thick lithium metal layer. AEROXIDE® Alu 130 particles were dissolved in 1,2-dimethoxyethane (DME, CH 10 O2) to obtain a first solution with a solid content of 5 wt %. Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP (supplied by Sigma-Aldrich, weight average molecular weight (Mw): approximately 400,000 g / mol) was also dissolved in DME to obtain a second solution with a solid content of 5 wt %. Molecular weights were measured using the ISO 16014 standard.

[0084] Both the first and second solutions were stirred vigorously for several hours and then mixed under stirring to produce a mixture with a 4:1 (by weight) ratio of alumina to PVDF-HFP copolymer. This mixture was coated onto the lithium metal layer by solvent casting. Specifically, the raw mixture slurry was stirred with a magnetic stirrer in a 20 mL volumetric sample vial and then coated onto the metal layer using a pen brush to form a mixed slurry layer covering the lithium metal layer. After the coating was applied, the lithium metal layer with the mixed slurry layer was heated on a hot plate at 70 °C for 30 minutes to evaporate the solvent and form an electrode plate including a lithium metal layer and a coating layer. The electrode plate forms a protective layer with a thickness of about 10 μm during the initial battery cycles. The ASEI is formed on the electrode surface of a secondary battery as a result of a chemical reaction between the electrolyte and the electrode material during the initial battery cycles and serves as a protective layer against further reactions.

[0085] Comparative Example 6 The same procedure was followed as described in Comparative Example 1, except that instead of AEROXIDE® Alu 130, Alu 130 805 aluminum oxide was used.

[0086] Comparative Example 7 The same procedure was followed as described in Comparative Example 1, except that aluminum oxide Alu 200 was used instead of AEROXIDE® Alu 130. After mixing the first and second solutions, the coating slurry was not stable for long-term storage, but the coating process was still carried out as soon as the coating slurry was prepared.

[0087] Comparative Example 8 The same procedure was followed as described in Comparative Example 1, except that instead of AEROXIDE® Alu 130, magnesium oxide, MgO-01, was used.

[0088] Comparative Example 9 The same procedure was followed as described in Comparative Example 1, except that magnesium oxide, MgO-08, was used instead of AEROXIDE® Alu 130. After mixing the first and second solutions, the mixed solution underwent a chemical reaction and the color of the mixed solution turned black, so no further testing was performed.

[0089] Example 2 The same procedure was followed as described in Comparative Example 1, except that magnesium oxide, MgO 805, was used instead of AEROXIDE® Alu 130. After mixing the first and second solutions, a stable dispersion was obtained with the surface-modified magnesium oxide particles.

[0090] Comparative Example 10: The Li-Cu foil was not coated with a protective layer. The Li-Cu was used as it is as an electrode. Specifically, a 12 μm Cu foil was used, and a 100 μm Li layer was laminated on top of it.

[0091] Fabrication of Li-Li symmetric cells using ether-type liquid electrolytes A 1 M solution of lithium bis(fluorosulfonyl)imide in 1.2:3 mol / mol=1,2-dimethoxyethane:1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether was used as the electrolyte composition.

[0092] The first coated electrode plate, a polypropylene-polyethylene-polypropylene (PP / PE / PP) separator (Celgard® 2320, supplied by Celgard Inc.) with a thickness of approximately 10-20 μm, and a second (same as the first) electrode plate were arranged in that order (with the metal compound coating layer of each electrode plate facing the separator) and sealed in a CR2032 coin cell.

[0093] Electrochemical characterization (cell cycle test) Electrochemical cycling tests were performed at room temperature using CR2032 type coin cells in an Arbin BT2000 battery tester. The voltage vs. time (cycle) profile during galvanostatic cycling of Li-Li cells is related to the stability and failure of the electrodes. The voltage profile of Li stripping and coating of the Li-Li symmetric cell was measured at 1.0 mAh / cm 2 The measurement was performed at a current density of 1000 Ω.

[0094] FIG. 5 shows the results of the current density test using AEROXIDE® Alu 130 (Comparative Example 5) as a filler in the protective layer on the Li layer at a current density of 1 mA / cm 2 The polarization voltage was applied in cycles of 1000 s.

[0095] FIG. 6 shows the results of the current density test using Alu 130 805 (Comparative Example 6) as a filler for the protective layer on the Li layer at a current density of 1 mA / cm 2 The polarization voltage was applied in cycles of 1000 s.

[0096] FIG. 7 shows the results of the current density test using Alu 200 (Comparative Example 7) as a filler for the protective layer on the Li layer at a current density of 1 mA / cm 2 The polarization voltage was applied in cycles of 1000 s.

[0097] FIG. 8 shows the results of a current density test using MgO-01 (Comparative Example 8) as a filler in the protective layer on the Li layer at a current density of 1 mA / cm 2 The polarization voltage was applied in cycles of 1000 s.

[0098] FIG. 9 shows the results of using MgO 805 (Example 10) as a filler for the protective layer on the Li layer at a current density of 1 mA / cm 2 The polarization voltage was applied in cycles of 1000 s.

[0099] FIG. 10 shows the current density of 1 mA / cm without a protective layer (Comparative Example 10). 2 The polarization voltage was applied in cycles of 1000 s.

[0100] FIG. 11 shows a current density of 1 mA / cm according to an embodiment. 2The polarization voltage after 200 cycles is shown in red. Table 2: Average polarization voltage at 200 cycles for coin cells with and without protective layer metal compounds / PVDF-HFP in ether-type electrolyte as shown in Figure 6.

[0101] [Table 2]

[0102] The coated electrode plate of Example 2 showed the most stable cycling performance and the lowest polarization voltage, which means that the resistance of the cell using surface-modified magnesia can provide stable coating dispersion and stable electrochemical performance in lithium metal batteries due to the composition of the protective layer with magnesia particles and PVDF-HFP in a weight ratio of 4:1.

[0103] Although the present invention has been described with reference to specific embodiments, the provided embodiments are not intended to limit the scope of the invention. Those skilled in the art, after reading this disclosure, may conceive many other variations of the described embodiments, as well as other embodiments of the invention, that do not depart from the scope of the invention as defined in the appended claims.

[0104] Reference Code List 8 Metal foil 10 metal layer 11 electrodes 14 Coating Layer OB Organic Binder MC metal compound 102, 104, 106 processes 400 Electrical or Electronic Devices 40 batteries 16 Separator 18 Separator Coating 20 Active materials 22 Electrode plate 24 Electrolytes

Claims

1. A composition for a coating layer of an electrode of a lithium battery, comprising an organic binder and a metal compound selected from the group consisting of hydrophobic surface-modified fumed magnesium oxide, hydrophobic surface-modified fumed lithium-doped magnesium oxide, hydrophobic surface-modified fumed magnesium phosphate, or a mixture thereof, the metal compound comprises agglomerates of primary particles, In the composition, the weight ratio of the metal compound to the organic binder is 0.1 to 10; 11. A composition wherein the binder is selected from the group consisting of poly(vinylidene fluoride), copolymers of vinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), poly(ethylene oxide), poly(methyl methacrylate), poly(ethyl acrylate), poly(vinyl chloride), poly(urethane), poly(acrylonitrile), poly(ethylene glycol), polypropylene glycol, poly(ethylene glycol-co-propylene glycol-co-ethylene glycol), poly(propylene glycol-co-ethylene glycol-co-propylene glycol), polysiloxanes, poly(oxyethylene)methacrylate, poly(ethylene glycol)diacrylate, poly(propylene glycol)diacrylate, poly(ethylene glycol)dimethacrylate, poly(propylene glycol)dimethacrylate, poly(ethylene glycol)dimethyl ether, poly(ether amines), copolymers of ethylene and vinyl acetate, carboxymethyl cellulose, poly(imides), and mixtures thereof.

2. 2. The composition of claim 1, wherein the weight ratio of said metal compound to said organic binder is from 0.2 to 9.5, more preferably from 0.3 to 9.0, even more preferably from 0.4 to 8.5, even more preferably from 0.5 to 8.0, even more preferably from 0.8 to 7.0, and most preferably from 1.0 to 6.

0.

3. the tap density of the metal compound is 20 g / L to 1,000 g / L, preferably 20 g / L to 200 g / L, more preferably 25 g / L to 150 g / L, even more preferably 28 g / L to 130 g / L, and most preferably 30 g / L to 120 g / L; The composition according to claim 1 or claim 2, wherein the packing density is measured according to DIN ISO 787-11:1995.

4. The composition according to any one of claims 1 to 3, wherein the surface-modified metal compound has a methanol wettability of greater than 5 vol.%, preferably between 10 vol.% and 80 vol.%, more preferably between 15 vol.% and 70 vol.%, even more preferably between 20 vol.% and 65 vol.%, and most preferably between 25 vol.% and 60 vol.%, measured as described herein.

5. further comprising a lithium salt mixed with said binder and said metal compound; the lithium salt is selected from the group consisting of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium triflate, lithium bis(perfluoroethylsulfonyl)imide (LiN(SO2CF2CF3)2), lithium nitrate, lithium bis(oxalo)borate, cyclo-difluoromethane-1,1-bis(sulfonyl)imide, cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide, and mixtures thereof; and / or the metal compound is modified to be hydrophobic with a surface treatment selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes, and mixtures thereof; The carbon content of the hydrophobic metal compound is preferably 0.1% by weight to 15.0% by weight, more preferably 0.5% by weight to 12.0% by weight, even more preferably 1.0% by weight to 10.0% by weight, and most preferably 1.5% by weight to 8.0% by weight; The composition according to any one of claims 1 to 4, wherein the carbon content is determined by elemental analysis according to EN ISO 3262-20:2000 (chapter 8).

6. An electrode for a lithium battery, the electrode (11) comprising a coating layer (14) formed on a metal layer (10) of the electrode (11), the coating layer (14) comprising the composition according to any one of claims 1 to 5.

7. The electrode according to claim 6, wherein in the coating layer 14, the weight ratio of the metal compound MC to the organic binder OB is 0.1 to 10, preferably 0.2 to 9.5, more preferably 0.3 to 9.0, even more preferably 0.4 to 8.5, even more preferably 0.5 to 8.0, even more preferably 0.8 to 7.0, and most preferably 1.0 to 6.

0.

8. 8. The electrode according to claim 6 or claim 7, further comprising a lithium salt added to the coating layer, and / or the coating layer has a thickness of 0.1 μm to 300 μm, more preferably 0.5 μm to 100 μm, even more preferably 1 μm to 50 μm, and most preferably 2 μm to 20 μm.

9. preparing at least one mixture comprising an organic binder OB and a metal compound MC, thereby preparing a first mixture (102), the binder is selected from the group consisting of poly(vinylidene fluoride), copolymers of vinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), poly(ethylene oxide), poly(methyl methacrylate), poly(ethyl acrylate), poly(vinyl chloride), poly(urethane), poly(acrylonitrile), poly(ethylene glycol), polypropylene glycol, poly(ethylene glycol-co-propylene glycol-co-ethylene glycol), poly(propylene glycol-co-ethylene glycol-co-propylene glycol), polysiloxanes, poly(oxyethylene)methacrylate, poly(ethylene glycol)diacrylate, poly(propylene glycol)diacrylate, poly(ethylene glycol)dimethacrylate, poly(propylene glycol)dimethacrylate, poly(ethylene glycol)dimethyl ether, poly(ether amines), copolymers of ethylene and vinyl acetate, carboxymethyl cellulose, poly(imides), and mixtures thereof; the metal compound is selected from the group consisting of hydrophobically surface-modified fumed magnesium oxide, hydrophobically surface-modified fumed lithium-doped magnesium oxide, hydrophobically surface-modified fumed magnesium phosphate, or mixtures thereof; The metal compound comprises a strong aggregate of primary particles, wherein the weight ratio of said metal compound to said organic binder in said composition is 0.1 to 10; - coating said first mixture onto the surface of the metal layer (10) to form a pre-coating layer (104); and - drying and / or curing said pre-coating layer (106) to form a coating layer (14). A method for producing the electrode (11) according to any one of claims 6 to 8, comprising:

10. the at least one mixture comprises a first mixture and a second mixture; the first mixture includes the metal compound particles and a first solvent, the second mixture comprises the organic binder, a second solvent, and optionally a lithium salt; the first solvent and the second solvent are the same or different; the first mixture preferably comprises from 1% to 70% by weight, more preferably from 3% to 60% by weight, even more preferably from 5% to 50% by weight, and most preferably from 7% to 45% by weight of the metal compound, and from 30% to 99% by weight, more preferably from 40% to 97% by weight, even more preferably from 50% to 95% by weight, and most preferably from 55% to 93% by weight of the solvent; said second mixture comprising 0.1% to 90% by weight, preferably 0.5% to 50% by weight, more preferably 1% to 20% by weight, even more preferably 2% to 10% by weight of said organic binder and 10% to 99.9% by weight, preferably 50% to 99.5% by weight, more preferably 80% to 99% by weight, even more preferably 90% to 98% by weight of said solvent; The method of claim 9 , wherein curing the coating mixture comprises a chemical reaction, a physical curing, or a combination thereof.

11. Method according to claim 9 or claim 10, wherein the drying and / or curing step (106) is preferably carried out at a temperature between 0°C and 500°C, more preferably between 5°C and 400°C, more preferably between 10°C and 300°C, more preferably between 20°C and 200°C, in the presence of air or with the exclusion of oxygen, preferably under a protective gas atmosphere of nitrogen or argon, under standard pressure or under reduced pressure, e.g. under vacuum.

12. said metal compounds being obtained by a pyrolysis process, including flame oxidation, flame hydrolysis and / or flame pyrolysis of starting materials in a hydrogen flame and / or an oxygen flame; The method according to any one of claims 9 to 11, wherein the starting material of the metal compound is an organic and / or inorganic metal compound such as a metal chloride, metal nitrate, metal acetate, metal carboxylate, etc.

13. The metal compound is obtained by flame spray pyrolysis; vaporizing a metal precursor, such as a metal chloride, and reacting it in a flame generated by the reaction of hydrogen and oxygen to produce a compound of said metal in the form of particles; The metal compound comprises a strong agglomerate of primary particles, some of which have a BET specific surface area of ​​1 m2 as measured by nitrogen adsorption according to the Brunauer-Emmett-Teller method in accordance with DIN 9277:2014. 2 / g to 500m 2 / g, more preferably 20m 2 / g to 400m 2 / g, and even more preferably 40m 2 / g~350m 2 / g, most preferably 50m 2 / g to 300m 2 / g, The number average strongly agglomerated particle size d50 is less than 2 μm, preferably 20 nm to 1 μm, more preferably 30 nm to 800 nm, even more preferably 40 nm to 600 nm, and most preferably 50 nm to 500 nm; 13. The method according to any one of claims 1 to 12, wherein the number average particle size d50 is measured in an aqueous dispersion by dynamic light scattering (DLS).

14. The metal compound is obtained by a pyrolysis method followed by an ultrasonic method, thereby breaking down weak agglomerates and some strong agglomerates to obtain a powder having a small particle size and a narrow particle size distribution; Preferably, the metal compound after the ultrasonic method is a mixture of 5% by weight of the particles and 95% by weight of a 0.5 g / L aqueous sodium pyrophosphate solution, and then ultrasonically treated at 25° C. for 300 seconds. The number average strongly aggregated particle diameter d50 measured by dynamic light scattering (DLS) is 50 nm to 1000 nm, more preferably 100 nm to 700 nm, and even more preferably 150 nm to 500 nm; The method according to any one of claims 1 to 13, wherein the metal compound is a mixture of 5 wt% of the particles and 95 wt% of a 0.5 g / L aqueous solution of sodium pyrophosphate, and the span (d90-d10) / d50 of the particles measured by dynamic light scattering (DLS) after ultrasonic treatment for 300 seconds at 25°C is preferably 0.4 to 1.2, more preferably 0.5 to 1.1, and even more preferably 0.6 to 1.

0.

15. A lithium battery comprising the electrode (11) according to any one of claims 6 to 8.

16. 16. An apparatus comprising the lithium battery of claim 15, and comprising an electric or electronic device such as a mobile phone, an electronic watch, a camera, a key fab, a laptop computer, a desktop computer, a computer pad, a power tool, a vacuum cleaner, an electric lawn mower, a robot, an electric appliance, an electric plane, and an electric car.

Citation Information

Patent Citations

  • Composite metal lithium negative electrode and preparation method thereof

    CN109473627A

  • Lithium metal battery

    US20170062829A1

  • Polymer protecting layer, lithium metal negative electrode, lithium secondary battery

    US20170301920A1

  • Negative electrode for lithium metal battery, method of preparing negative electrode, and lithium metal battery including the same

    US20180316051A1

  • Anode electrode and electrochemical device containing the same

    US20200106103A1